CAUSES OF THE ORIGIN OF APHTHRITIS DISEASE - Xodjayeva Naimaxon Umirzaqovna; Qobulov Nematillo Raxmatillo òĝli; Abdug`aniyev Abdukarim Abdug`affor o`g`li (Web of Journals Publishing, 2024)
Aphthritis, commonly referred to as canker sores, is a multifactorial condition that affects the oral mucosa, causing discomfort and impacting quality of life. This article explores the causes of aphthritis, providing a comprehensive analysis of genetic, environmental, immunological, and microbiological factors. By synthesizing current research, this study offers insights into the disease's origins and suggests avenues for prevention and management.
Keywords: Aphthritis, canker sores, oral mucosa, genetic predisposition, immunological factors, microbiota, environmental triggers.